Strong-field interactions in atoms and nanosystems: advances in fundamental science and technological capabilities of ultrafast sources - Summers, Adam M. (Kansas State University, 2019)
Modern laser sources can produce bursts of light that surpass even the fastest molecular vibrations. With durations this short even moderate pulse energies generate peak powers exceeding the average power output of the entire globe. When focused, this can result in an ultrafast electric field greater than the Coulomb potential that binds electrons to nuclei. This strong electric field strips electrons away from atoms in a process known as strong-field ionization. The first experimental realization of photoionization with intense laser pulses occurred only a few years after the invention of the laser. Yet, despite decades of intensive investigation, open questions remain. At the same time, the knowledge gained has led to the creation of multiple exciting fields such as attoscience, femtochemistry, and ultrafast nano-photonics. In this thesis I present my work to advance the fundamental understanding of intense, ultrafast light-matter interactions as well as efforts to expand the technological capabilities of ultrafast light sources and measurement techniques. This includes the photoionization process of atoms and nanoparticles subject to intense, mid-infrared laser fields. The resulting photoelectron emission is measured, with high precision, in a velocity map imaging spectrometer. Other parts of this thesis detail my work on the generation and characterization of non-Gaussian optical pulses. Femtosecond Bessel beams are used to drive and study high harmonic generation with the ultimate goal of creating a compact, high-flux XUV source. Further studies include few-cycle pulses and the carrier-envelope phase, specifically methods of locking and tagging the carrier-envelope phase. A single-shot, all optical tagging method is developed and directly compared to the standard tagging method, the carrier-envelope phase meter. Finally, both experimental and computational studies are presented investigating the ultrafast thermal response cycle of nanowires undergoing femtosecond heating.
Keywords: Physics; Atomic Molecular and Optical Physics; Ultrafast Optics; Strong-Field Physics; Nanophotonics; Lasers